(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2024)
This essay suggests that the structure and poetic elements of the anonymous medieval Catalan “novela”, Curial y Güelfa, exemplify a mingling of Arabic elements. Taking into account the feminine sensibility that is always present in the Mozarabic poetic tradition, the possibility is presented of analysing this work like a novel with a traditional oriental structure that at the same time represents the inverse corpus (transformation from poetry to prose) of a long woman’s song or cantiga de amigo